Triazido[tris(2-pyridyl-κN)methylamine]cobalt(III) - Xia Liu; Lujiang Hao (Acta Crystallographica Section E, 2008)
The title compound, [Co(N3)3(C16H14N4)], was synthesized by hydrothermal reaction of [Co(NH3)6](NO3)3, NaN3 and tris(2-pyridyl)methylamine. The structure contains two independent complexes in the asymmetric unit, with closely comparable geometry. The CoIII atoms are hexacoordinated by three N atoms from the tridentate tris(2-pyridyl)methylamine ligands and three azide ions in a fac arrangement. N—H...N hydrogen bonds are formed between the amino group and the uncoordinated terminal N atoms of the azide ligands.